Multimodal evaluation of the bloodstream alteration before and after combined revascularization for Moyamoya disease - Cao, Lei; Yuan, Xiaoli; Dong, Yang; Wang, Zeming; Guo, Mengguo; Li, Dongpeng; Zhang, Manxia; Yan, Dongming; Yang, Bo; Li, Hongwei (Frontiers in Neurology, 2023)
Objective This study aimed to explore the hemodynamic changes before and after anastomosis in patients with Moyamoya disease (MMD) using multiple models. Methods We prospectively enrolled 42 MMD patients who underwent combined revascularization. Intraoperative FLOW800 was performed before and after anastomosis, and parameters was collected, including maximum intensity, delay time, rise time, slope, blood flow index, and microvascular transit time (MVTT). Additionally, preoperative and postoperative hemodynamic parameters were measured using color Doppler ultrasonography (CDUS), including peak systolic velocity, end-diastolic velocity, resistance index (RI), pulsatility index (PI), and flow volume. Subsequently, the correlation between FLOW800 and CDUS parameters was explored. Results A total of 42 participants took part with an average age of 46.5 years, consisting of 19 men and 23 women. The analysis of FLOW800 indicated that both the delay time and rise time experienced a substantial decrease in both the recipient artery and vein. Additionally, the MVTT was found to be significantly reduced after the surgery (5.7 ± 2.2 s vs. 4.9 ± 1.6, p = 0.021). However, no statistically significant differences were observed among the other parameters. Similarly, all postoperative parameters in CDUS hemodynamics exhibited significant alterations in comparison to the preoperative values. The correlation analysis between FLOW800 and CDUS parameters indicated a significant association between MVTT and RI and PI, no significant relationships were found among the other parameters in the two groups. Conclusion The hemodynamic outcomes of the donor and recipient arteries demonstrated significant changes following bypass surgery. The parameter of time appears to be more precise and sensitive in assessing hemodynamics using FLOW800. Multiple evaluations of hemodynamics could offer substantial evidence for perioperative management.